Peacekeeper Fatalities and Force Commitments to UN Operations. (May 2021) - Levin, Andrew
To what extent do peacekeeper fatalities affect states' contributions to UN operations? While the deaths of peacekeepers are thought to be a factor in states' decisions to reduce the magnitude of their participation in a mission, not all states respond similarly to peacekeeper fatalities. I hypothesize that democracies and wealthy countries are likely to be more sensitive to peacekeeper deaths than their non-democratic and poorer counterparts. Analyses of UN peacekeeping operations between 1990 and 2011 confirm that peacekeeper fatalities generally have a negative effect upon the size of countries' contributions to peacekeeping operations, and that wealthy countries are likely to make larger decreases to their contributions than poorer countries. There is less evidence, however, that democracies are more sensitive to peacekeeper fatalities than non-democracies.